1987
DOI: 10.1002/clc.4960101017
|View full text |Cite
|
Sign up to set email alerts
|

Influence of acute hyperglycemia on left ventricular function in diabetics assessed by echocardiography

Abstract: Summary: Myocardial dysfunction in diabetes mellitusis reversed by proper correction of metabolic changes. To assess the role of hyperglycemia on cardiac dysfunction, 50 g of dextrose were intravenously infused to 15 subjects with stable type 2 diabetes. Echocardiographic measurements were made at 0,60, 120, 180, and 240 minutes. In spite of the high levels of blood glucose reached in diabetics, left ventricular ejection fraction, fractional shortening, and stroke volume did not experience significant changes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…A previous study reports that glucose levels acutely increased by glucose infusion in T2D patients with normal LVEF had no effect on global LV function [31]. However, in the present studies more sensitive measurements based on tissue-Doppler velocity unambiguously demonstrated that left ventricular contractile function was higher during hyperglycemia than during normoglycemia.…”
Section: Discussionsupporting
confidence: 46%
“…A previous study reports that glucose levels acutely increased by glucose infusion in T2D patients with normal LVEF had no effect on global LV function [31]. However, in the present studies more sensitive measurements based on tissue-Doppler velocity unambiguously demonstrated that left ventricular contractile function was higher during hyperglycemia than during normoglycemia.…”
Section: Discussionsupporting
confidence: 46%
“…Some of the previously conducted studies have shown that hyperglycemia following a glucose infusion in diabetic patients with normal LVEF, had no effect on the global LV function [43] detected by standard echocardiography, while we used more sophisticated method (strain analysis) for detection of LV systolic function. Studies in animal models indicated that acute hyperglycemia could suppress LV diastolic function and influences mitochondrial energy signaling [44], or induces changes in polyol metabolic pathway with consequently increase in oxidative stress leading to myocardial contractile dysfunction [45].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study in patients with T2D and healthy controls, 50 g dextrose intravenous infusion increasing PG to 27 mmol/L in the patients with T2D did not have a significant effect on LVEF. 4 However, the statistical method applied (comparing absolute means instead of change from baseline) may have masked an effect, and mean LVEF did rise from 63% to 66%, whereas it was unchanged in controls, in whom PG remained <10 mmol/L. In patients with type 1 diabetes (T1D), acute normalization of PG leads to a decline in LVEF, whereas normalization of long-term glycaemic control as evaluated by HbA1c had no effect on LVEF.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, hyperglycaemia with abundant glucose availability and enhanced endogenous insulin production may promote glucose utilization, potentially enhancing cardiac function. An improved systolic function during hyperglycaemia in patients with T2D has been indicated in previous studies, although no effect on left ventricular ejection fraction (LVEF) was observed, and consequently the practical implications are uncertain 3,4 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation